2001
DOI: 10.1046/j.1439-0485.2001.01731.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Habits of Trisopterus minutus capelanus (Gadidae) Off the Eastern Coast of Spain (Western Mediterranean)

Abstract: Abstract. The stomach contents of poor cod, Trisopterus minutus capelanus (Lacepède), were taken at monthly intervals off the eastern coast of the Gulf of Valencia (Spain). A total of 1276 were analyzed to determine diet according to fish size and season. The basic food consists of crustaceans (Mysidacea and Decapoda) and teleosts. Feeding habits varied with size: decapods and fishes were more abundant in the stomachs of larger specimens. Little seasonal variation in food habits was recorded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
(34 reference statements)
4
13
1
Order By: Relevance
“…Our data are consistent with those of Vivó and Sanz () and Morte et al. (), who reported that smaller T. draco specimens in the Gulf of Valencia consumed more mysids, often switching to decapods and telosts as the fish increased in length. These results are in line with an ecological strategy that reduces intraspecific competition for food in a population.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data are consistent with those of Vivó and Sanz () and Morte et al. (), who reported that smaller T. draco specimens in the Gulf of Valencia consumed more mysids, often switching to decapods and telosts as the fish increased in length. These results are in line with an ecological strategy that reduces intraspecific competition for food in a population.…”
Section: Discussionsupporting
confidence: 93%
“…draco collected from the Gulf of Valencia by Morte et al. () support this generalistic behaviour. Vivó and Sanz (), who sampled in the same area, also reported a diversity of benthic prey species.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This indicates that the observed seasonal variations in food ingestion are related to fluctuations of the prey in the environment. Although no data are available for the study area with regard to prey availability, previous studies in the Gulf of Valencia on the feeding habits of several fish point out that several prey species, such as L. gracilis, A. glaber, L. depurator, G. rhomboides and L. friesii , occurred more frequently in the stomach contents of benthic fishes (Vivó & Sanz, 1989; Redón et al , 1994; Morte et al , 1997a, 1997b, 1999a, 1999b). The observed seasonal change, besides the diet variations due to fish size, could also be due to depth of sampling.…”
Section: Discussionmentioning
confidence: 94%
“…Only Salpa sp. (Andersen & Nival 1988), Cotylorhiza tuberculata (Pérez-Ruzafa et al 2002) and Sarpa salpa (Peirano et al 2001) forage directly on the primary sources, while the remaining jellyfish (Malej 1989) and fish (Roux 1986, Cardinale et al 1997, Morte et al 1999, Stergiou & Karpouzi 2002 Statistical analyses. Multivariate analysis of variance (MANOVA) with 4 fixed factors (decaying blades of Posidonia oceanica, epiphytes, POM and Cystoseira balearica) was used to test whether the 4 sources considered shared a common bivariate isotopic signal.…”
Section: Methodsmentioning
confidence: 99%